Ultrasound guided thoracic dorsal root ganglia pulsed radiofrequency verified by fluroscopy for patients with lung cancer and metastatic thoracic cage pain: a randomized controlled study - Dina Kamel Abdel Maksoud; Sahar Ahmed El Karadway; Nagwa Ahmed Ibrahim; Dina Nabil Abbbas (Alexandria Journal of Medicine)
Background Dorsal root ganglions (DRG) are promising target for patients with cancer lung and thoracic cage metastasis; those who get inadequate pain relief on pharmacotherapy. The current study aimed to investigate the effect of ultrasound guided pulsed radiofrequency (PRF) of thoracic DRG on metastatic thoracic cage pain intensity and impact of pain on daily life of patients with lung cancer.Materials and Methods 30 patients with lung cancer thoracic cage metastatic pain were randomized equally to receive active PRF plus 0.5 ml lidocaine 2% for each thoracic DRG modulation (group 1) or non-active PRF plus 0.5 ml of lidocaine 2% (group 2). The primary outcome was pain intensity post intervention. The secondary outcomes were impact of pain on patient’s daily life measured by brief pain inventory – short form (BPI-SF), patient’s satisfaction with pain relief measured by five-level Likert-type scale, accuracy of ultrasound in detecting needle tip position and complications.Results VAS for pain decreased significantly in group 1 compared to group 2 one week post intervention (p < 0.001). The worst, least, average pain and pain right now in addition to impact of pain on mood, sleep and enjoyment of life all were less in group 1 compared to group 2 up to 3 months post intervention (p < 0.001). Pain effect on relations with others decreased significantly in group 1 than group 2 two weeks post intervention (p = 0.021). The influence of pain on patient’s general activity and walking ability did not differ significantly between the studied groups. 60% of patients in group 1 were either very satisfied or satisfied with pain relief compared with none of patients in group 2 one week post intervention. No technical serious side effects were detected.Conclusions Ultrasound guided PRF verified by fluoroscopy of thoracic DRG decreases metastatic thoracic cage pain intensity, minimizes the impact of pain on patient’s mood, sleep and enjoyment of life and increases satisfactions with pain relief.